GC/MS analysis, antimicrobial and in vitro anti-cholinesterase activities of the essential oil from Buddleja asiatica (Bangladesh Journal of Pharmacology, 2015)
Buddleja asiatica essential oil from the leaves by hydrodistillation was subjected to gas chromatography/mass spectrometery analysis which revealed the presence of 17 constituents out of which 14 were identified as: four monoterpenes hydrocarbons, four oxygenated monoterpenes, one hydrocarbon sesquiterpenes and five oxygenated sesquiterpenes. The major constituent being found was 1,8-cineole (38.1%) while β-sinensal, 1, 10-seco-1-hydroxy-calamenen-10-one and α-phellandrene were found to be in 11.8%, 10.2% and 5.8%, respectively. The essential oil exhibited 66% strong antibacterial activity against Shigella boydii while in fungicidal assay, it revealed an outstanding 79% inhibition against Aspergillus flavus. The essential oil showed outstanding acetylcholinesterase (IC50 5.2 μM) and butyrylcholinesterase inhibitory effect (IC50 27.9 μM) as compared to standard drugs respectively.